2014
DOI: 10.1109/tnnls.2013.2285242
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Batch Processes Using Explicitly Time-Dependent Artificial Neural Networks

Abstract: A neural network architecture incorporating time dependency explicitly, proposed recently, for modeling nonlinear nonstationary dynamic systems is further developed in this paper, and three alternate configurations are proposed to represent the dynamics of batch chemical processes. The first configuration consists of L subnets, each having M inputs representing the past samples of process inputs and output; each subnet has a hidden layer with polynomial activation function; the outputs of the hidden layer are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…It is difficult to propose an accurate mathematical model of noises of PMSM, because their generation involves multiple physical coupling interactions with strong non-linearity and extreme complexity [21][22][23][24][25]. In this paper, the PMSM SQ is considered as a black-box problem.…”
Section: Neural Network Model Of Sq Prediction Of Pmsmmentioning
confidence: 99%
“…It is difficult to propose an accurate mathematical model of noises of PMSM, because their generation involves multiple physical coupling interactions with strong non-linearity and extreme complexity [21][22][23][24][25]. In this paper, the PMSM SQ is considered as a black-box problem.…”
Section: Neural Network Model Of Sq Prediction Of Pmsmmentioning
confidence: 99%
“…(16) and (19) respectively, and the coefficient matrix A is of dimensions nyÂnx. A schematic representation of the proposed modeling approach is shown in Fig.…”
Section: Pddf Model Developmentmentioning
confidence: 99%
“…Most of the control and optimal control studies based on ANN have been reported based on hybrid neural network approaches [14,15], whereas very few attempts have been made to use purely data driven neural networks to model batch processes [16] and for batch process optimization [17]. Also there have been a couple of attempts to address the issue of batch to batch variations in semi batch process optimal control [18,19].…”
Section: Introductionmentioning
confidence: 99%